Glosa do wyroku Sądu Apelacyjnego w Poznaniu z dnia 12 czerwca 2024 r., I AGa 280/22 - Żok, Krzysztof (PRAWO i WIĘŹ, 2025)
The purpose of this commentary is to examine the artist’s resale right (droit de suite) from the perspective of inheritance law. According to the discussed judgment, this right is not included in the author’s iunheritance for two reasons. First, the droit de suite is closely linked to the deceased author. Secondly, the artist’s resale right passes to the heir outside the succession, i.e. by virtue of singular succestion mortis causa. Furthermore, the judgment indicates that the right in question passes only to the direct heirs of the author. However, the analysis presented in the commentary undermines this conclusion